Biclonal Gammopathy in Multiple Myeloma with Vertebral Compression Fracture - Amit Ranjan; Rukmini Mysore Srikantiah; K Ashok Prabhu; Urmila N Khadilkar (Journal of Clinical and Diagnostic Research, 2018)
Biclonal gammopathy is characterised by simultaneous appearance of two different monoclonal proteins. A rare case of Biclonal gammopathy [IgA lambda(λ) and IgG kappa (κ)] and D10 vertebral fracture in a 46-year-old male patient with complaints of sudden onset low back ache while lifting a heavy object, which was aggravated for one month presented to the Orthopaedic department of our institute. Magnetic Resonance Imaging (MRI) of dorso-lumbar spine revealed anterior wedge collapse of D10 vertebral body with enhancement causing compressive myelopathy. Bone marrow biopsy of D10 vertebrae was performed and the features were suggestive of plasma cell myeloma. Serum protein electrophoresis indicated biclonal gammopathy and immunofixation electrophoresis showed intense IgAλand faint IgGκ. The patient was started on chemotherapy following a decompression surgery of the D10 vertebra.